Characterization of the resistome in Lactobacillus genomic sequences from the human gut. (September 2022) - Moradi, Jale; Fathollahi, Matin; Halimi, Shahnaz; Alvandi, Amirhooshang; Abiri, Ramin; Vaziri, Siavash; Rezaei, Akram
Highlights: Resistome analysis of 321 Lactobacillus genomic sequences derived from the human gut. Identification of four high-frequency resistance genes, three of which were associated with acquired resistance, including poxtA (17.4%), lmrB (12%), and BJP-1 (7.7%). The first report of BJP-1 in lactobacilli suggests that it is transferred from soil microbiota to humans. Highlighting the 'One Health' perspective, early detection of a new reservoir would control the global spread of antibiotic resistance to other environments. ABSTRACT: Objectives: The gut is a complex environment inhabited by a wide range of bacterial species. Lactobacillus species constitute a significant proportion of this environment and, due to their mobile genetic elements such as plasmids and transposons, are more likely to acquire and transfer antibiotic resistance genes through horizontal gene transfer (HGT). Methods: The current study obtained and analysed 321 genome assemblies to determine the prevalence of intrinsic and acquired antibiotic resistance genes (ARGs) among Lactobacillus species colonizing the human gastrointestinal tract. Results: A total of four high-frequency resistance genes were identified, including dfra42 (42%), poxtA (17.4%), lmrB (12%), and BJP-1 (7.7%); aside from dfra42, which is an intrinsic resistance gene, the other genes are acquired resistance genes. PoxtA was found in several different species, mainly in L. paracasei, whereas BJP-1 and lmrB were found in only one species, L. rhamnosus . IS5-like elements family transposase flanked 11% and 8% of detected lmrB and BJP-1, respectively, while a variety of insertion sequences surrounded 22% of identified poxtA. Furthermore, to the best of our knowledge, this is the first report of BJP-1 in lactobacilli that would suggest it has transferred from soil microbiota to humans. Conclusion: According to the 'One Health' perspective, early detection of a new reservoir would control the global spread of the antibiotic-resistant bacterial species among the three environments, which include humans, the environment, and animals. Finally, the study's findings may then highlight the possibility of lactobacilli acquiring or transmitting resistance to other species within or outside the human intestine.